2005
DOI: 10.1111/j.1399-0004.2005.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

LMNA mutation position predicts organ system involvement in laminopathies

Abstract: The underlying disease mechanisms likely include mutation effects on the nuclear envelope and on interactions between lamins and transcription factors. At the same time, can a simple genomic attribute -- for instance, mutation position within the LMNA sequence -- predict the complex phenotypic effects? In order to assess this, hierarchical cluster analysis (HCA) was used for assembling 16 laminopathies into two classes based on organ system involvement. Ninety-one reported causative LMNA mutations in these lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 15 publications
2
77
1
3
Order By: Relevance
“…Hegele using hierarchical cluster analysis for assembling laminopathies according to phenotypic similarity found that LMNA mutations at the 5 0 of codon 416 were seen more frequently in laminopathies with cardiac or neurological involvement, and in addition several overlapping syndromes, while mutations at the 3 0 of codon 423 are more likely to be associated with simple partial lipodystrophy, progeria syndrome, or mandibuloacral dysplasia (34). Our findings are in agreement with this, as the mutations found at the 3 0 to the nuclear localization signal were in patients with simple partial lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Hegele using hierarchical cluster analysis for assembling laminopathies according to phenotypic similarity found that LMNA mutations at the 5 0 of codon 416 were seen more frequently in laminopathies with cardiac or neurological involvement, and in addition several overlapping syndromes, while mutations at the 3 0 of codon 423 are more likely to be associated with simple partial lipodystrophy, progeria syndrome, or mandibuloacral dysplasia (34). Our findings are in agreement with this, as the mutations found at the 3 0 to the nuclear localization signal were in patients with simple partial lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with haploinsufficiency or homozygous mutations have also been reported [4,6]. A hierarchical cluster analysis revealed interesting genotype/phenotype correlations [13]. There was a trend for mutations in the alpha-helical regions to cause muscular dystrophy, while mutations in globular regions were more likely to have been responsible for lipodystrophies.…”
Section: Introductionmentioning
confidence: 97%
“…FPLD2 является одной из 16 различных нозологических форм ламинопатий (так называемых аллельных серий) [5], раз-вивающихся в результате более 100 различных мутаций в гене LMNA, из них 12 заболеваний наследуются по аутосомно-доми-нантному типу, а 4 остальных -по аутосомно-рецессивному [6]. При этом расположение мутации в первичной генетической по-следовательности ДНК LMNA влияет на выраженность и харак-тер патологических изменений.…”
Section: рис 3 генеалогическое древо семьи хunclassified